Enhancing Advanced Writing Proficiency in Indonesian Elementary Education: Integrating Collaborative Pedagogy and AI-Based Innovation - Islamiyah, Mufidah; Hamzah, Rahma Ashari; Harmin, Harmin (Reforma: Jurnal Pendidikan dan Pembelajaran, 2025)
Writing instruction in Indonesian elementary schools often receives less emphasis compared to other language skills, despite its importance in developing students’ ability to think critically and communicate effectively. This study explores how advanced writing instruction—specifically for students in Grades 4–6—can be enhanced through practical strategies and technological support. Using qualitative content analysis of 58 academic sources published between 2019 and 2024, the study identifies key teaching approaches such as text modeling, collaborative writing, and project-based learning. The findings reveal that successful writing instruction is shaped by three main factors: teachers’ instructional strategies, students’ cognitive readiness, and the integration of engaging tools such as artificial intelligence. For example, AI-driven learning, including the use of tools like ChatGPT, helps students generate ideas and receive real-time feedback, thereby enhancing creativity and motivation. However, challenges remain, such as limited student vocabulary, abstract thinking skills, and the continued use of conventional teaching methods. The study concludes that a student-centered, creative, and technology-supported approach is essential for improving writing outcomes. It recommends sustained teacher training and curriculum support to align instructional practices with the demands of 21st-century literacy.